THEORIES ABOUT THE ADVANTAGES OF APPLYING AXIOLOGICAL KNOWLEDGE TO THE EDUCATIONAL PROCESS IN THE HISTORY OF WESTERN PEDAGOGY (Web of Teachers: Inderscience Research, 2025)
Looking at the history of Western pedagogy, the issue of the axiological approach and the implementation of a system of values in the educational process has been a constant and relevant topic. These theories play a central role in the continuous development of ideas and methods. Axiology is the science of values, and the importance of values in human life and their role in the development of society has long been the subject of attention of scientists and educators. In the West, the idea of introducing axiological knowledge into the educational process has been a leading one in many pedagogical schools and methods.